Anastatica hierochuntica, an Arabidopsis Desert Relative, Is Tolerant to Multiple Abiotic Stresses and Exhibits Species-Specific and Common Stress Tolerance Strategies with Its Halophytic Relative, Eutrema (Thellungiella) salsugineum - Eshel, Gil; Shaked, Ruth; Kazachkova, Yana; Khan, Asif; Eppel, Amir; Cisneros, Aroldo; Acuna, Tania; Gutterman, Yitzhak; Tel-Zur, Noemi; Rachmilevitch, Shimon; Fait, Aaron; Barak, Simon (Frontiers in Plant Science, 2017)
The search for novel stress tolerance determinants has led to increasing interest in plants native to extreme environments – so called “extremophytes”. One successful strategy has been comparative studies between Arabidopsis thaliana and extremophyte Brassicaceae relatives such as the halophyte Eutrema salsugineum located in areas including cold, salty coastal regions of China. Here, we investigate stress tolerance in the desert species, Anastatica hierochuntica (True Rose of Jericho), a member of the poorly investigated lineage III Brassicaceae. We show that A. hierochuntica has a genome approximately 4.5-fold larger than Arabidopsis, divided into 22 diploid chromosomes, and demonstrate that A. hierochuntica exhibits tolerance to heat, low N and salt stresses that are characteristic of its habitat. Taking salt tolerance as a case study, we show that A. hierochuntica shares common salt tolerance mechanisms with E. salsugineum such as tight control of shoot Na+ accumulation and resilient photochemistry features. Furthermore, metabolic profiling of E. salsugineum and A. hierochuntica shoots demonstrates that the extremophytes exhibit both species-specific and common metabolic strategies to cope with salt stress including constitutive up-regulation (under control and salt stress conditions) of ascorbate and dehydroascorbate, two metabolites involved in ROS scavenging. Accordingly, A. hierochuntica displays tolerance to methyl viologen-induced oxidative stress suggesting that a highly active antioxidant system is essential to cope with multiple abiotic stresses. We suggest that A. hierochuntica presents an excellent extremophyte Arabidopsis relative model system for understanding plant survival in harsh desert conditions.